ELBOW JOINT RADIOGRAPHY EXAMINATION PROCEDURE IN POST OPEN REDUCTION INTERNAL FIXATION CASES IN THE RADIOLOGY INSTALLATION OF KENDAL DISTRICT HOSPITAL - Utami, Lucky Restyanti Wahyu; Alfiani, Novita (Journal of Applied Health Management and Technology, 2024)
The elbow joint is the joint between the humerus and radioulna. One of the disorders that occurs in the musculoskeletal system is a fracture. A fracture is an event that breaks the continuity of bone tissue. One action that can be taken to treat bone fractures is surgery, open reduction internal fixation. One of the supporting examinations to see the condition of the bones after the open reduction internal fixation procedure is a radiological examination with conventional radiography. The aim of this research is to determine the procedure for radiographic examination of elbow joints in cases of post open reduction internal fixation in the Radiology Installation of Kendal District Hospital. The type of research used is descriptive qualitative research with a case study approach. The research results obtained were that the radiographic examination procedure for the elbow joint in post open reduction internal fixation cases did not require any special patient preparation, the patient was only asked to remove objects in the elbow joint area to be examined so as not to interfere with the radiograph results such as elastic bandage locks. Tools and materials used in the examination include an x-ray machines, examination table, imaging plate measuring 18x24 cm, a chair for the patient to sit in and a computed radiography device. The projections used are anteroposterior projection and lateral projection.